Is gold a safe haven, a hedge or a diversifier for BRICS investors? - Neves, Kayllen (My University, 2021)
Gold has been around for thousands of years and its uses have evolved over time from a precious metal to a means of exchange and now as a financial asset that is traded in many forms. The characteristics of gold have been studied extensively over the years for developed markets, but few papers have looked at the metals characteristics for developing and emerging markets. This research seeks to analyse the characteristics of gold in order to establish whether the metal could act as a safe haven, a hedge or a diversifier for BRICS investors. This study replicates the methodology of Baur and Lucey (2010) and uses two principal regression models to analyse the characteristics of gold as a safe haven, a hedge or a diversifier for BRICS equity and bond markets. The property of gold as a safe haven is widely accepted, although there is few academic research on this especially within developing and emerging markets. The findings of this research show that gold is a hedge on average for Brazilian, Russian and Indian equity markets, while gold is only a hedge for Chinese equity markets at the 2,5 percent quantile. Gold however, was not found to be a hedge on average for South African equity markets. In relation to BRICS bond markets, gold was found to be a hedge for all BRICS bond markets except for the Chinese bond market. The findings of this research in relation to the safe haven property of gold for BRICS investors was not present. This implies that when the BRICS markets face extreme market turmoil, holding gold in BRICS investors’ portfolios will provide no protection against their falling bond and equity markets.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investment to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: BRICS investors; Financial asset; Gold mining; SDG-8: Decent work and economic growth